Schools of Chinese, Vietnamese, Burmese, Laotian, Thai and Khmer languages - A. N. Aleksachin (MGIMO University Press, 2014)
School of teaching Chinese, Vietnamese, Burmese, Laotian, Thai and Khmer languages functions under the same title as the department, which was established in 1954 at the Department of Chinese Language of the Moscow Institute of Oriental Studies. MGIMO graduates with the knowledge of the Chinese language are successfully working in the structural units of the Russian foreign Ministry and all over the world, in various government agencies and major companies. Currently, the number of students studying Chinese language is 128 people as a first language.